2016
DOI: 10.3390/s16122053
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Computing Model of Activity Recognition on WSN Movement Data for Ubiquitous Healthcare Measurement

Abstract: Ubiquitous health care (UHC) is beneficial for patients to ensure they complete therapeutic exercises by self-management at home. We designed a fuzzy computing model that enables recognizing assigned movements in UHC with privacy. The movements are measured by the self-developed body motion sensor, which combines both accelerometer and gyroscope chips to make an inertial sensing node compliant with a wireless sensor network (WSN). The fuzzy logic process was studied to calculate the sensor signals that would e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We can preprocess the measured data using a fuzzy algorithm from our previous study, which suggested the transformation process to select the possible features [39]. The features include the relative acceleration, angular velocity, and angle of the motion with respect to the original position of the wristband.…”
Section: Methods and Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…We can preprocess the measured data using a fuzzy algorithm from our previous study, which suggested the transformation process to select the possible features [39]. The features include the relative acceleration, angular velocity, and angle of the motion with respect to the original position of the wristband.…”
Section: Methods and Modelingmentioning
confidence: 99%
“…In addition, the adaptive neuro-fuzzy inference system (ANFIS) that repetitively tunes the FIS in a training-based algorithm has been suggested to optimize the inference ability of the adopted features [36,37]. Therefore, the FIS can be one of the appropriate methods to recognize the human activity for healthcare measurement since the activity subject performs the characteristics of behavior with the inferable features [38,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcevic et al [ 31 ] have used a combination of accelerometers, gyroscopes, and magnetometers on both wrists of the subject and achieved a 91.74% activity recognition accuracy on a set of 11 activities. Other experiments have used accelerometers on different parts of the body, such as the right part of the chest and the left thigh [ 32 ], on both wrists and the torso [ 33 ] with added RFID wristband readers in [ 34 ] to monitor human-object interaction. Raad et al [ 35 ] have opted for the use of RFID tags on ankle bracelets for localization and tracking of elders with Alzheimer’s.…”
Section: Offline Activity Recognitionmentioning
confidence: 99%
“…In this paper, ANFIS technology is used to design a fire detection control system and reduce false alarms. ANFIS technology has been used in mobile robot navigation [16], healthcare monitoring systems [17], air conditioning control [18], flood susceptibility modeling [19], and many other applications. In recent times, fiberoptic sensors were used for structural fire engineering [20], however, there is a need for true fire identification.…”
Section: Introductionmentioning
confidence: 99%